Assessing changes in the availability and readiness of health facilities to provide modern family planning services in Bangladesh: Insights from Bangladesh Health Facility Surveys, 2014 and 2017 - Rajon Banik; Syed Toukir Ahmed Noor; Abu Bakkar Siddique; Md. Sabbir Ahmed Mayen; Anindita Saha; Ashiquzzaman; Lubna Hossain; Abu Sayeed; Nondo Saha; Md. Akib Al- Zubayer; Md. Lutful Kader; Ema Akter; et al. (PLoS ONE, 2025)
Background Modern family planning plays a vital role in reducing unintended pregnancies, a major reproductive health issue worldwide. Access to modern family planning services is essential for empowering women to have greater control over their reproductive health and rights. In Bangladesh, there remains an unmet need for modern family planning services among reproductive-aged women. Assessing the capacity of health facilities to address these unmet needs for modern family planning is crucial. Objectives The objective of this study was to assess the changes in the availability and readiness of health facilities to provide modern family planning services in Bangladesh between 2014 and 2017, and identify factors associated with facility readiness. Methods We performed a secondary analysis of cross-sectional data from Bangladesh Health Facility Surveys (BHFS) conducted in 2014 and 2017. Availability was determined based on whether a facility offered at least one modern family planning method, and facility readiness was measured following the Service Availability and Readiness Assessment (SARA) manual. Descriptive statistics with 95% confidence intervals (CIs) were reported, and Poisson regression models were used to identify factors associated with health facility readiness. Findings The percentage of facilities offering modern family planning services increased significantly from approximately 81% (95% CI: 78, 85) in 2014 to 89% (95% CI: 87, 91) in 2017. The availability of oral pills, injectables, and male condoms increased over this period, while the availability of long-acting reversible contraceptives (LARCs) slightly decreased, and permanent methods (PMs) remained nearly unchanged. The overall mean readiness score of health facilities declined slightly, from about 54 (95% CI: 52, 56) in 2014 to 51 (95% CI: 50, 53) in 2017. Upazila Health Complexes and Maternal and Child Welfare Centers had significantly higher readiness compared to District Hospitals in 2017. Facilities that performed routine quality assurance activities, ensured 24-hour staff coverage, maintained a system for reviewing clients’ feedback, and provided family planning services regularly demonstrated significantly higher readiness to provide modern family planning services in both 2014 and 2017. Regional disparities were also observed; facilities in rural areas had significantly lower readiness than those in urban areas, and facilities from the Rangpur division showed significantly higher readiness compared to those in Dhaka in both survey years. Conclusion The findings indicate a significant increase in the availability of health facilities offering modern family planning services in Bangladesh; however, a slight decline has been observed in their overall mean readiness score. Ensuring an adequate provision of equipment and supplies, expanding access to LARCs and PMs, and improving staff capacity through regular training are essential. Furthermore, strengthening quality assurance activities and investing in rural facilities are required for improving the facility readiness and advancing progress toward achieving SDG 3.7 targets of universal access to modern family planning services in Bangladesh.